down fall of pakistan economy due to terrorism - khalid, afnan mehmood (Advances in Social Sciences Research Journal, 2017)
The main purpose of this work is to find out the factors that will effect on Pakistan economy that will become the main reason of downfall of the economy of Pakistan due to terrorism. Last few years, Pakistan is facing the different problems like terrorism is one of the big issues. Not only Afghan War affect Pakistan but also affected by various Sectarian Conflict, religious and linguistic conflicts which have increased terrorists’ activities. Using data on terrorism on global terrorism database and analysis for the period of 2006-2015.The analysis shows that terrorism has badly effected the economy of Pakistan. However, study finds that different tools are used to remove the uncertainty by using high-security system and infrastructure.